2019
DOI: 10.1002/jbm4.10118
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Observational Cohort Study to Evaluate the Effects of Bisphosphonate Exposure on Bone Mineral Density and Other Health Outcomes in Osteogenesis Imperfecta

Abstract: Osteogenesis imperfecta (OI) is characterized by low bone mass and bone fragility. Using data from a large cohort of individuals with OI from the Osteogenesis Imperfecta Foundation's linked clinical research centers, we examined the association between exposure to bisphosphonate (BPN) treatment (past or present) and lumbar spine (LS) areal bone mineral density (aBMD), fractures, scoliosis, and mobility. From 466 individuals, we obtained 1394 participant‐age LS aBMD data points. Though all OI subtypes were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 27 publications
0
22
0
1
Order By: Relevance
“…Genotypic information was used to classify patients when available. For participants without a molecular diagnosis, the site principal investigator and project principal investigator were required to be in agreement with regard to the subtype of OI based on specific criteria 1 , 23 - 26 . Data were collected uniformly at each site and the quality was assessed at the data entry point.…”
Section: Methodsmentioning
confidence: 99%
“…Genotypic information was used to classify patients when available. For participants without a molecular diagnosis, the site principal investigator and project principal investigator were required to be in agreement with regard to the subtype of OI based on specific criteria 1 , 23 - 26 . Data were collected uniformly at each site and the quality was assessed at the data entry point.…”
Section: Methodsmentioning
confidence: 99%
“…Bisphosphonates not only increase lumbar spine (LS) BMD but also improve bone structures, increase mobility and reduce fracture risk [ 4 , 6 ]. In 2019 Bains et al in a cohort multicenter study on 299 individuals with OI type I (a mild form of disease), revealed that people who were receiving bisphosphonates, BMD and mobility had increased, fracture rate and scoliosis was decreased in comparison with the group who did not took bisphosphonates [ 21 ]. There is no unanimous view as to when bisphosphonate treatment should be initiated for individuals with OI [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates, which act by inhibiting osteoclast activity and bone resorption, are the mainstay of pharmacologic treatment in pediatric patients with OI. Bisphosphonates have been shown to consistently improve bone mineral density in patients with OI (9,49,53) and, to some extent, reduce fracture incidence (9,51). During growth, they have a beneficial effect on reshaping vertebrae that have compression fracture deformities (9,54).…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…During growth, they have a beneficial effect on reshaping vertebrae that have compression fracture deformities (9,54). Other than the improvement in bone mass and architecture in growing children, the beneficial effects of bisphosphonates have not been conclusive, although a recent study indicated a positive effect on fracture incidence, scoliosis probability, and mobility in preadolescent patients with OI type I (53). Common side effects include acute phase infusion reaction (most typically during the first infusion) and transient hypocalcemia.…”
Section: Bisphosphonatesmentioning
confidence: 99%